2022
DOI: 10.1021/acsanm.2c02707
|View full text |Cite
|
Sign up to set email alerts
|

MXene/Multiwalled Carbon Nanotube/Polymer Hybrids for Tribopiezoelectric Nanogenerators

Abstract: Wearable portable electronic devices have become an indispensable part of the modern lifestyle because of their smart, convenient, and fashionable features. Fiber-based nanogenerators are generally used as energy supply systems in wearable portable electronic devices. In the present work, poly(vinylidene fluoride) (PVDF) and poly(L-lactic acid) (PLLA) were used in triboelectric layers of hybrid tribopiezoelectric nanogenerators (HNGs). Twodimensional MXenes and one-dimensional multiwalled carbon nanotubes (MWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…The resulting hydrogen bonds between anions on the MXene surface and hydrogen atoms of PVDF chains can create a dipole that responds to an applied electric field, so the strong electrostatic interaction between PVDF chain and MXene effectively promotes the formation of a piezoelectric phase and induces a strong interface coupling effect and increases its electronegativity. 47,48 Figure 4a shows the 3D basement structure and the formation process of the S-TENG at different folding stages. FEP is chosen as the base of the S-TENG due to its excellent durability, low friction coefficient, good heat resistance, low cost, lightweight, and so on.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting hydrogen bonds between anions on the MXene surface and hydrogen atoms of PVDF chains can create a dipole that responds to an applied electric field, so the strong electrostatic interaction between PVDF chain and MXene effectively promotes the formation of a piezoelectric phase and induces a strong interface coupling effect and increases its electronegativity. 47,48 Figure 4a shows the 3D basement structure and the formation process of the S-TENG at different folding stages. FEP is chosen as the base of the S-TENG due to its excellent durability, low friction coefficient, good heat resistance, low cost, lightweight, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Such an excellent output performance of the MXene-PVDF film could be attributed to the excellent metal electronic conductivity and high electronegative property, as well as rich surface end groups. The resulting hydrogen bonds between anions on the MXene surface and hydrogen atoms of PVDF chains can create a dipole that responds to an applied electric field, so the strong electrostatic interaction between PVDF chain and MXene effectively promotes the formation of a piezoelectric phase and induces a strong interface coupling effect and increases its electronegativity. , …”
Section: Resultsmentioning
confidence: 99%
“…Ds‐time curves are shown in Figure 14, and data related to smoke density are shown in Table 7. According to the European standard EN45545‐2, 63 the flame retardant grade and parameter calculation formula for rail transit materials were introduced in the previous study 64 . By analyzing the data, it can be found that the Ds of EP‐15 and EP‐20 decreased significantly compared with those of pure EP, and both obtained HL1 grade.…”
Section: Resultsmentioning
confidence: 99%
“…20 Recently, 2D nanomaterials having a large surface area have been used to facilitate such a self-pole process for enhancing the electroactive phases of PVDF and maximizing the piezo output of the miniaturized nanogenerator devices. 21 The layered structure of these 2D nanomaterials is also suitable for the development of the β phase in PVDF as they provide more interfacial area for interaction through the volume. Addition of these nanomaterials enhances the mechanical properties of the PVDF composites, improving the performance of the nanogenerator.…”
Section: Introductionmentioning
confidence: 99%